Path-length-multiplexed scattering-angle-diverse optical coherence tomography for retinal imaging - Wang, Bingqing (2013)
A low-resolution path-length-multiplexed scattering angle diverse optical coherence tomography (PM-SAD-OCT) is constructed to investigate the scattering properties of the retinal nerve fiber layer (RNFL). Low-resolution PM-SADOCT retinal images acquired from a healthy human subject show the variation of RNFL scattering properties at retinal locations around the optic nerve head. The results are consistent with known retinal ganglion cell neural anatomy and principles of light scattering. Application of PM-SAD-OCT may provide potentially valuable diagnostic information for clinical retinal imaging.